Examining heterogeneity in mentoring: Associations between mentoring discussion topics and youth outcomes. Issue 3 (28th September 2022) - Alwani, Noor A.; Lyons, Michael D.; Edwards, Kelly D.
Abstract: The current study aims to apply a staged approach to document heterogeneity in discussions in mentoring relationships, chiefly, discussion topics from weekly mentoring sessions with undergraduate women mentors ( n  = 40), then link each of the eight topics (relationships with friends, family, teachers, and romantic relationships, as well as goals, academic skills, academic problems, and hopes for the future) to developmental outcomes for middle school girls ( n  = 41) who participated in a school‐based mentoring program. In doing so, the authors hope to better understand the mechanisms that influence variability in mentoring treatment effects. Mentoring dyads engaged in unstructured one‐on‐one sessions and structured group meetings across the 2018−2019 academic year. The primary predictors for this study are weekly mentor‐reported discussion topics and activities addressed during unstructured one‐on‐one mentoring sessions, with 11 social‐emotional, academic, and behavioral outcomes measured via pre‐ and postsurveys administered by research assistants to mentees during the fall and spring. A series of 11 path analyses indicate small to moderate associations, both beneficial and negative, between key discussion topics, such as hopes for the future, family relationships, and goals, and several mentee‐reported outcomes of interest at the end of the intervention, including extrinsic motivation, life satisfaction, and self‐esteem. Study findings provide information about heterogeneity in mentoring practices to inform how various mechanisms of mentoring (e.g., discussions focused on relationships, goals and skills, and strengths) influence developmentally‐relevant effects for youth.